(untitled) (Bioagro, 2025)
Understanding the molecular mechanisms of sugar accumulation in the taproot of sugar beet (Beta vulgaris L.) is essential for enhancing sugar production. In this study, we analysed growth parameters and gene expression profiles of taproots collected at 50 (S1), 90 (S2), 160 (S3), and 330 (S4) days after sowing (DAS). Growth analysis revealed that the length, width, and weight of the taproots increased over time, with a particularly rapid weight gain observed between 50 and 160 DAS. Sugar content increased sharply from 50 to 90 DAS, gradually rose until 160 DAS, and then tended to decrease up to 330 DAS. Differential expression analysis identified 4,560, 4,764, and 4,781 differentially expressed genes (DEGs) in comparisons between S1:S2, S1:S3 and S1:S4, respectively. Among these, 3,255 DEGs were common across all comparisons, with 1,345 genes upregulated and 1,909 genes downregulated. Focusing on sugar metabolism, we identified 48 DEGs related to sucrose metabolism enzymes and sugar transport proteins. Cluster analysis divided these DEGs into two groups based on their expression patterns: Class I genes including those encoding sucrose synthase, sucrose transporter proteins, fructokinase, and hexokinase were downregulated compared to S1, while Class II genes including sucrose transporter proteins, sucrose-phosphate synthase, fructokinase, and hexokinase were upregulated. These findings contribute to understanding of the gene expression associated with sugar accumulation during sugar beet taproot development and provide valuable insights for future genetic improvement aimed at increasing sugar content in sugar beet crops.